Avaliação radiográfica da perda óssea em implantes de dois ou mais elementos, instalados em região posterior de maxila e mandíbula: estudo retrospectivo - Salzedas, Luísa Machado [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The objective of the present study was to evaluate peri-implant bone loss in periapical radiographs in implants installed in the posterior region of maxilla and mandible rehabilitated by multiple fixed prosthesis. Fifty patients were examined, and periapical radiographs were performed using phosphor plate sensors that were scanned into the Apixia equipment and examined with Dental Master software. Bone loss was assessed by measuring mesial and distal surfaces of 161 implants with attached prosthesis. The results show that there was bone loss of 3.1mm in the maxilla and 3.74mm in the mandible. In addition, it was possible to observe that the greatest bone loss was given on the mesial surface of the implants, with an average of 3.50mm. Concerning the presence of alveolar mucosa or inserted gingiva, there was a mean of 2.98 mm of peri-implantar bone loss in the maxilla in the cases of inserted gingiva and 2.31 mm in the alveolar mucosa. In the mandible, there was 2.35mm of bone loss in the inserted gingiva and 3.46mm in the alveolar mucosa. According to the results, it was concluded that there was a higher bone loss in the implants attached by multiple fixed prosthesis, installed in the mandible posterior region, and in the mesial face, with a notable absence of gingiva inserted in the mandible

O presente trabalho teve por objetivo, avaliar por meio de radiografias periapicais, a perda óssea periimplantar em implantes instalados em região posterior de maxila e mandíbula reabilitadas por prótese fixa múltipla. Foram examinados 50 pacientes, e realizadas radiografias periapicais utilizando sensores de placa de fósforo que foram digitalizados no equipamento Apixia e examinados com o software Dental Master. Foi avaliado a perda óssea por meio de mensurações nas faces mesial e distal de 161 implantes com prótese unida, considerando ainda, o tipo de gengiva adjacente. Os resultados mostram que houve perda óssea de 3,1mm na maxila e 3,74mm na mandíbula. Além disso foi possível observar que a perda óssea maior foi dada na face mesial dos implantes, com média de 3,50mm.Com relação à presença de mucosa alveolar ou gengiva inserida, houve na maxila a média de 2,98mm de perda óssea periimplantar nos casos de gengiva inserida e 2,31mm em mucosa alveolar. Na mandíbula, houve 2,35mm de perda óssea em gengiva inserida e 3,46mm em mucosa alveolar. De acordo com os resultados obtidos, conclui-se que houve perda óssea maior nos implantes unidos por prótese fixa múltiplas, instalados na região posterior de mandíbula, e na face mesial, com ausência notória de gengiva inserida na mandíbula
Keywords: Implantes dentários; Reabsorção óssea; Maxila; Mandíbula; Dental implants